Compositional quality of food obtained with solid state fermentation: potato and carrot - Rodríguez-Salgado, Angela Mireya; Borrás-Sandoval, Luis Miguel; Rodríguez-Molano, Carlos Eduardo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The fermentation indicators and compositional quality of food made with the solid-state fermentation of potatoes and carrots were analyzed in order to make use of foods that do not meet the requirements of consumers. Three treatments were formulated by varying the potato:carrot ratio mixed with wheat bran and corn cabbage. A microbiological analysis was performed at 0, 24 and 96 hours; the pH, crude protein (PC), ash (CZ), ethereal extract (EE), crude fiber (FC), neutral detergent fiber (FDN) and acid detergent fiber (FDA) were monitored at 0, 24, 48, 72 and 96 hours. Acidification was observed between sampling at 0 and 96 hours, with values ranging from 5.68 to 4.46, 5.73 to 4.46 and 5.69 to 4.33 for the treatments with the potato:carrot ratios 20:20, 25:25 and 30:30, respectively. Similarly, a reduction of dry matter (P<0.05) and PC increase (P<0.05) were observed from 20.1 to 26.7%, 21.1 to 27.1% and 25, 4 to 27.9%, respectively for the previous ratios. No significant statistical difference was found in the variables CZ, MS, EE, FDN, FDA or FC; a significant growth of lactic acid bacteria (LAB) counts and an absence of Salmonella were evident. The proportionality in the PC increase with the potato:carrot ratios was viable with the increase of the drying material, such as wheat bran and corn cabbage.